ANALISIS PPN DAN PPH BADAN PADA PERUSAHAAN KONSTRUKSI PT. ACG - Tiolemba, Febrianne; Widjaja, Purnamawati Helen (Jurnal Paradigma Akuntansi, 2024)
This research was conducted with the aim of knowing the imposition of income tax rates and corrections contained in the Tax Return period of Value Added Tax on companies. This research was conducted with an interview process to get data on the company's financial statements during 2020 and other information related to what is needed from the company. The results of this study show that the company has applied the final income tax rate in accordance with the applicable provisions and the company also experiences more payment every month so that it can make restitution or compensation.